The history of sport in Kalisz in 1918-1939. Outline of issues - Julian Jaroszewski (Jan Długosz University in Częstochowa, 2023)
Regaining of independence by Poland enabled the development of sports movement in Kalisz. Until 1926 sport developed mainly under the influence of tradition and interests of Kalisz residents. After the May coup, by managing grants and sports facilities, a decisive influence on development of sport was gained by state authorities. The factors which inhibited the development of sports movement in Kalisz were the lack of training staff and insufficient number of sports facilities. Sports which enjoyed the greatest popularity in Kalisz during the interwar period were football, cycling and rowing. The highest level of training among footballers was demonstrated by teams of Sports Association "Prosna" and Kalisz Sports Club which took part in local games. Rowers from Kalisz Rowing Association belonged to the best in Poland (in 1934 1st place in the table of Polish Association of Rowing Clubs). Jerzy Koszutski, a rower from Kalisz, had the great honour of representing the national colours during the 9th Olympic Games in Amsterdam in 1928. A lot of emotions were aroused by boxing matches, athletics and table tennis. Fencing, horse riding and shooting sports were promoted by military and police environment as well as paramilitary organizations for utilitarian reasons.